2015
DOI: 10.1093/jee/tov126
|View full text |Cite
|
Sign up to set email alerts
|

Ipsenol, Ipsdienol, Ethanol, and α-Pinene: Trap Lure Blend for Cerambycidae and Buprestidae (Coleoptera) in Pine Forests of Eastern North America

Abstract: In 2007-2008, we examined the flight responses of wood-boring beetles (Coleoptera: Cerambycidae and Buprestidae) to multiple-funnel traps baited with the pine volatiles, ethanol, and α-pinene [85% (-)], and the bark beetle pheromones, racemic ipsenol and racemic ipsdienol. Experiments were conducted in mature pine stands in Canada (Ontario and New Brunswick) and the United States (Arkansas, Florida, Michigan, New Hampshire, North Carolina, Ohio, Tennessee, and Wisconsin). At each location, traps were deployed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…These compounds, combined with the synergistic action of ethanol, became the basis for the development of attractants for use in monitoring the number of H. abietis beetles that can cause economic damage to forest crops in Europe (Moore, ; Nordlander, ; Skrzecz, ; Wilson & Day, ; Zumr & Stary, ). Further studies confirmed that ethanol and α‐pinene function as attractants for many species of beetles, not only from the family Curculionidae, which includes many species of beetle that are damaging to reforestations, but also many species of bark and wood‐boring insects in the Cerambycidae and Buprestidae families (Miller et al, ). In 2003, Bichäo, Borg‐Karlson, Araújo, and Mustaparta () identified the P. notatus (= P. castaneus ) neuronal receptors that respond to the monoterpenes (mainly α‐pinene, β‐pinene and 3‐carene) secreted by P. pinaster .…”
Section: Discussionmentioning
confidence: 87%
“…These compounds, combined with the synergistic action of ethanol, became the basis for the development of attractants for use in monitoring the number of H. abietis beetles that can cause economic damage to forest crops in Europe (Moore, ; Nordlander, ; Skrzecz, ; Wilson & Day, ; Zumr & Stary, ). Further studies confirmed that ethanol and α‐pinene function as attractants for many species of beetles, not only from the family Curculionidae, which includes many species of beetle that are damaging to reforestations, but also many species of bark and wood‐boring insects in the Cerambycidae and Buprestidae families (Miller et al, ). In 2003, Bichäo, Borg‐Karlson, Araújo, and Mustaparta () identified the P. notatus (= P. castaneus ) neuronal receptors that respond to the monoterpenes (mainly α‐pinene, β‐pinene and 3‐carene) secreted by P. pinaster .…”
Section: Discussionmentioning
confidence: 87%
“…Other records that included seasonal activity and county occurrence data were retrieved from published reports (Meyer 1937;Dillon & Dillon 1941, 1947Linsley 1962aLinsley ,b, 1963Linsley , 1964Dillon 1956a,b,c;Linsley & Chemsak 1972, 1976, 1984, 1995TCEIR 1972;McCauley & Eanes 1987;MacRae 2000;Gryzmala 2006;Schiefer & Newell 2010;Tindall et al 2010;Leavengood & Chapman 2014;Vlasak 2014;Miller et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Ma Other records that included seasonal activity and county occurrence data were retrieved from published reports (Meyer 1937;Dillon & Dillon 1941, 1947Linsley 1962aLinsley ,b, 1963Linsley , 1964Dillon 1956a,b,c;Linsley & Chemsak 1972, 1976, 1984, 1995TCEIR 1972;McCauley & Eanes 1987;MacRae 2000;Gryzmala 2006;Schiefer & Newell 2010;Tindall et al 2010;Leavengood & Chapman 2014;Vlasak 2014;Miller et al 2015).…”
Section: Methodsmentioning
confidence: 99%